The regulations supporting socio-economic initiative in takaful operations - Hassan, Rusni; Harun, Hafiza (International Association of Islamic Banks Karachi, Pakistan., 2019)
Takaful operation in Malaysia has proven their credibility through the remarkable achievement in the market structure and net contribution income. As a financial product, takaful is one of the key tools in wealth protection. As the dedicated institutions which are authorized to operate in providing Shariah-compliant protection coverage to the community, Takaful Operators are subject to relevant regulations and procedures. These regulations are important in providing a guided supervision and to ensure the interest of every stakeholder are preserved. This research paper applies the literature review based methodology that demonstrates the nature of takaful operations for society and nation. From the regulatory perspective, Bank Negara Malaysia plays its role through the introduction and enforcement of numerous rulings for takaful industry. The regulations such as Shariah Governance Framework, Islamic Financial Services Act, Takaful Operational Framework, Life Framework and Value-Based Intermediation are found to support takaful industry in achieving its operations’ objective of helping the community’s socio-economic environments.